Kinematics and muscle activity of the lower limb during single-leg stance on the two sides of the Togu Jumper - Mayer, Petra; Sebesi, Balázs; Vadász, Kitty; Laczkó, József; Zentai, Norbert; Balázs, Bence; Váczi, Márk (Frontiers in Physiology, 2023)
Purpose: The both sides-utilized Togu Jumper has been shown to be effective in improving postural control but there are no recommendations for the usage of the sides. Our aim was to examine leg muscle activity and kinematics in response to a single-leg stance on the two sides of the Togu Jumper and the floor. Methods: In 14 female subjects, linear acceleration of leg segments, segmental angular sway, and myoelectric activity of 8 leg muscles were recorded in the three stance conditions. Results: Except gluteus medius and gastrocnemius medialis , all muscles were more active when balancing on either Togu Jumper side compared to the floor (p < 0.001), but there was no difference between the two sides in any muscles. Linear acceleration was the greatest in the frontal plane on the flat Togu side in the case of the foot (p <0.001). Pelvis acceleration was unaffected by the balance conditions. Segmental angular sway was the greatest in the frontal plane, on the bladder side in the foot segment (p <0.001). No difference was found among the three conditions (all p > 0.05) in the case of the shank, thigh, and pelvis. Conclusion: The use of the two Togu Jumper sides produced different balance strategies in the foot segment and induced no difference in equilibrium procedures at the level of the pelvis.